Development and validation of a video on first aid for choking incidents in the school environment - Priscila da Silva Miranda; Liliane Faria da Silva; Emília Gallindo Cursino; Fernanda Garcia Bezerra Góes; Sandra Teixeira de Araújo Pacheco; Juliana Rezende Montenegro Medeiros de Moraes (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To develop and validate an educational video on first aid for choking incidents in children in the school environment. Method: Methodological study, conducted between 2021 and 2022, in six stages: search for themes through interviews with 13 teachers and staff members who work in early childhood education in Niterói; theoretical study; development of the video; validation with 17 expert judges; video adaptation and validation with 17 teachers and staff. The interviews were analyzed using the Iramuteq software and the validation through the concordance index, with a desirable value of 70%. Results: The animated video, lasting 4 minutes and 10 seconds, addressed the identification and management of the child experiencing choking and was validated with a concordance index of 97% among the judges and 96% with target audience. Conclusion: The video is a validated technology that can be used to develop educational practices with professionals in the school environment.